Sistem Informasi Pemasaran - Baihaki, Abdul Razak; Syamil, Muhammad; Rosita, Halimatu (Maliki Interdisciplinary Journal, 2025)
A marketing information system is a collection of individuals, devices and procedures that are organized and interact with each other, with the aim of creating an orderly and accurate flow of information, which is collected from internal and external sources of the company to be used as a basis for decision making in specific areas of management. marketing. This marketing information system can be described as being between the environment and the marketing office as its use. This article aims to prove that the data we collect through journals and books is appropriate. After discussing strategy and the relationship between Information Technology strategy and business strategy, we can plan a strategy based on business strategy, which includes Information Technology assessment and analysis, Information Technology planning and design, and Information Technology implementation and design. This research method uses secondary data from books, journals, documentation and the internet as a data collection method. To provide answers to the problem formulation, the required data is analyzed thoroughly and outlined in sub-chapters. Content analysis is a method used to analyze data. The research method known as content analysis or content review uses a series of procedures to draw valid conclusions from a book.